Developing Method based on Differentiated Instruction for Teaching Writing to Junior High School Students in Kediri - Masyhudianti, Ummy Khoirunisya' (LP. Ma'arif Janggan Magetan, 2026)
This study aims to develop a method based on Differentiated Instruction (DI) in teaching writing using adjusted GBA (Genre Based Approach) to Junior High School students in Kediri. This research employed a Research and Development design, utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants included one teacher and 35 students from a Junior High School in Kediri, selected through purposive sampling. Data were collected through interviews, questionnaires, observation, and document analysis, and analyzed qualitatively and quantitatively. The data validity was done by using triangulation technique. The results demonstrated that the adjusted Genre-Based Approach with Differentiated Instruction, incorporating songs, games, and differentiated content and products across BKOF, MOT, JCOT, and ICOT, is effective for both students and teachers, enhancing students' writing skills. Expert validation scores support the method, with pre-assessment and DI at 87.5% (exceeds expectations), method at 91.7% (exceeds expectations), and evaluation at 79.2% (meets expectations). The adjusted GBA method proved to be effective for teaching writing to improve students' writing scores, as demonstrated by the average post-test score of 85. Future research should explore the method’s applicability in senior high school, as well as longitudinal studies to assess its long-term impact on writing skills development.